Investigating the feasibility of tumour molecular profiling in gastrointestinal malignancies in routine clinical practice. (9th October 2017) - Moorcraft, S Y; Gonzalez de Castro, D; Cunningham, D; Jones, T; Walker, B A; Peckitt, C; Yuan, L C; Frampton, M; Begum, R; Eltahir, Z; Wotherspoon, A; Teixeira Mendes, L S; et al.
Abstract: Background: Targeted capture sequencing can potentially facilitate precision medicine, but the feasibility of this approach in gastrointestinal (GI) malignancies is unknown. Patients and methods: The FOrMAT (Feasibility of a Molecular Characterisation Approach to Treatment) study was a feasibility study enrolling patients with advanced GI malignancies from February 2014 to November 2015. Targeted capture sequencing (mainly using archival formalin-fixed paraffin-embedded diagnostic/resection samples) was carried out to detect mutations, copy number variations and translocations in up to 46 genes which had prognostic/predictive significance or were targets in current/upcoming clinical trials. Results: Of the 222 patients recruited, 215 patients (96.8%) had available tissue samples, 125 patients (56.3%) had ≥16 genes successfully sequenced and 136 patients (61.2%) had ≥1 genes successfully sequenced. Sample characteristics influenced the proportion of successfully sequenced samples, e.g. tumour type (colorectal 70.9%, biliary 52.6%, oesophagogastric 50.7%, pancreas 27.3%, P = 0.002), tumour cellularity (high versus low: 78.3% versus 13.3%, P ≤ 0.001), tumour content (high versus low: 78.6% versus 27.3%, P = 0.001) and type of sample (resection versus biopsy: 82.4% versus 47.6%, P ≤ 0.001). Currently, actionable alterations were detected in 90 (40.5%) of the 222 patients recruited (66% of the 136 patients sequenced) and 2 patients subsequently received a targeted therapy. The most frequently detected currently actionable alterations were mutations in KRAS, BRAF, TP53 and PIK3CA . For the 205 patients with archival samples, the median time to obtain sequencing results was 18.9 weeks, including a median of 4.9 weeks for sample retrieval and 5.1 weeks for sequencing. Conclusions: Targeted sequencing detected actionable alterations in formalin-fixed paraffin-embedded samples, but tissue characteristics are of critical importance in determining sequencing success. Routine molecular profiling of GI tumours outside of clinical trials is not an effective use of healthcare resources unless more targeted drugs become available. ClinicalTrials.gov identifier: NCT02112357